A three component-based van der Waals surface vertically designed for biomolecular recognition enhancement. (20th April 2021) - Hassan, Ayaz; Macedo, Lucyano J.A.; Mattioli, Isabela A.; Rubira, Rafael J.G.; Constantino, Carlos J.L.; Amorim, Rodrigo G.; Lima, Filipe C.D.A.; Crespilho, Frank N.
Highlights: Monolayer graphene was supported on Au modified SiO2 /Si substrate. The Au underneath sufficiently enhanced the electrochemical activity of graphene. Fc was adsorbed on top of graphene to develop a three component vdW surface. The developed three components vdW surface has enhanced surface sensitivity. The device showed a four-time higher sensitivity towards ds-DNA hybridization detection. Abstract: Graphene-based vertical electrodes may have applications in biomolecular recognition for producing low-cost biodevices with high electronic conductivity. However, they are unsuitable for measuring small interfacial capacitance variations because graphene is mostly composed of basal sp 2 carbon surface, which limits its sensitivity as an electrochemical biosensor. Herein, we introduce a monolayer graphene based three-component vertically designed (TCVD) device composed of ferrocene adsorbed on monolayer graphene supported on lithographically designed gold subsurface on silicon wafer. Ferrocene is the top layer that promotes reversible redox communication with the electrolyte, while graphene–gold is the strategically projected layer underneath. This system exhibits an enhanced chemical reactivity by allowing the electrochemical attachment of the larger amount of the organic functional groups on its surface and faster electrochemical response to an inner-sphere redox probe in the solution. Bader charge analysis indicated that gold donates electronic density to the graphene surface, thereby significantly increases the charge transfer exchange rate with ferrocene. Based on density functional theory (DFT) simulation and spectromicroscopy data, it was realized that the interaction between gold and graphene is through physical adsorption with a slight change in the Fermi's level of graphene. The TCVD device was used to detect the adsorption of double-stranded DNA and DNA hybridization in solutions. Based on capacitance calculation measurements, DNA hybridization in nanomolar range with sensitivity four times higher and limit of detection (LOD) three times lower as compared to Fc/Gr/SiO2 /Si, which was effortlessly detected. This result is promising since 3.0 µF cm −2 is the limit of quantum capacitance for bare graphene. Notably, these results open a new possibility for next-generation TCVD bioelectronics based on van der Waals surfaces, while further innovation and material scrutiny may lead to the achievement of TCVD devices with robust biomolecular recognition abilities. Graphical abstract: Image, graphical abstract